Pengaruh Pemanfaatan QRIS terhadap Pengelolaan Kas UMKM di Medan Marelan - Bunga Avrilia Ebena Limbong; Mei Hotma Mariati Munte; Rimbun C.D. Sidabutar (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to analyze the effect of the utilization of the Quick Response Code Indonesian Standard (QRIS) on cash management in Micro, Small, and Medium Enterprises (MSMEs) in Medan Marelan District. This research applies a quantitative approach with a causal associative design. Data were collected through questionnaires distributed to 100 MSME actors who have implemented QRIS in their business activities. The data analysis techniques employed include descriptive statistics, validity and reliability tests, classical assumption tests, and simple linear regression analysis using IBM SPSS. The results indicate that the utilization of QRIS has a positive and significant effect on MSME cash management. This is evidenced by a significance value of 0.000, which is lower than 0.05, and a t-value that exceeds the critical t-table value. In addition, the coefficient of determination shows that QRIS utilization explains a portion of the variance in cash management. These findings suggest that QRIS not only facilitates transaction processes but also improves efficiency in financial recording and enhances transparency. Therefore, QRIS plays an important role in supporting more effective and systematic cash management for MSMEs.